Gender Disparity Competence in Drafting Technology among Government Secondary Learning Institutions - Maria Rosario M. Avila; Patricio R. Malquisto (European Scientific Journal, ESJ, 2019)
This study determined the level of competencies between male and female students in drafting technology as a subject of Grade 8 in secondary schools in Leyte. It assessed the profile of the students along with their age, grade in drafting technology and family income. It also looked into their attitude and study and work habits towards drafting technology. Likewise, it looked into the level of competencies along the different areas such as: Freehand drawing, lettering, geometric construction, orthographic drawing, pictorial drawing, and commercial Arts. The descriptive survey research method was used in this study. It was conducted in selected public secondary learning institutions in Leyte, Philippines with 345 randomly chosen respondents. Structured questionnaires were administered to generate the needed primary data. Findings revealed that majority of the students were 14- 15 years old with satisfactory rating. They belong to families below poverty threshold. Both male and female students were moderately favourable towards drafting technology and exhibited satisfactory study and work habits. Their level of drafting competency was satisfactory having similar levels of competences for both male and female respondents. Inadequate drafting facilities were the top problems met by the students. In conclusion, both male and female students possessed good competency level in drafting technology course, exhibited moderately favourable attitudes and satisfactory in their study and work habits towards drafting technology. The study recommends that students should improve their attitude and study habits. State of the art facilities have to be provided by the administration to upgrade students’ knowledge and skills in drafting technology.